2010
DOI: 10.1007/s00429-010-0275-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of neural stem cells in the hippocampus of adult rats by custom-made Ad vectors

Abstract: Adult hippocampal neural stem cells (NSC) are an intriguing source for cell replacement or could serve as delivery vehicles for therapeutic genes. We recently reported selective transduction of adult mouse NSC in the DG by in vivo injection of GFP encoding adenoviral (Ad) vectors engineered to bind NSC-specific peptides. Here, we investigated the specificity of these peptide-tagged vectors in the adult rat DG, and whether they can be used to follow differentiation of infected cells over time. The virus-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Corroborating these findings, transthyretin (TTR), a thyroid hormone transporter predominantly produced by the CP [112], exhibits a gender-specific role in the control of neurogenesis in the SVZ that is restricted to a specific subdomain of the SVZ [181], which is in line with the gender-based differences in CP-derived TTR levels detected in the CSF [71,182]. Molecular heterogeneity linked to the receptor repertoire can be also observed between SVZ and SGZ, indicating intrinsic differences in the sensitivity of adult germinal centres to signalling factors presented via CSF [183,184]. This is supported by recent finding showing expression of LRP2, receptor for various morphogens, including BMPs and Wnts that were previously detected in CSF, to be restricted only to SVZ and devoid from SGZ.…”
Section: The Target Brain Regions Of Cp-csf Signallingsupporting
confidence: 59%
“…Corroborating these findings, transthyretin (TTR), a thyroid hormone transporter predominantly produced by the CP [112], exhibits a gender-specific role in the control of neurogenesis in the SVZ that is restricted to a specific subdomain of the SVZ [181], which is in line with the gender-based differences in CP-derived TTR levels detected in the CSF [71,182]. Molecular heterogeneity linked to the receptor repertoire can be also observed between SVZ and SGZ, indicating intrinsic differences in the sensitivity of adult germinal centres to signalling factors presented via CSF [183,184]. This is supported by recent finding showing expression of LRP2, receptor for various morphogens, including BMPs and Wnts that were previously detected in CSF, to be restricted only to SVZ and devoid from SGZ.…”
Section: The Target Brain Regions Of Cp-csf Signallingsupporting
confidence: 59%
“…Thus, the most important challenge is to develop Ad-derived gene delivery systems with high efficiency through target cell selectivity, in particular under in situ conditions (Reetz et al 2014). Our recent endeavors in the generation of Ad vectors that specifically target stem/progenitor cells in the body have focused on linking selective peptides to viral particles that direct the virus to specific or yet unknown receptors on the surface of stem cells (Hildebrandt et al 2010;Schmidt et al 2007). Using an Ad-PEGylation approach, we demonstrated that a short artificial peptide selected by phage display, which specifically binds neural precursor cells derived from the hippocampal area of adult mice or rats, was highly effective in targeting NSPCs after virus administration into the brain (Hildebrandt et al 2010;Schmidt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent endeavors in the generation of Ad vectors that specifically target stem/progenitor cells in the body have focused on linking selective peptides to viral particles that direct the virus to specific or yet unknown receptors on the surface of stem cells (Hildebrandt et al 2010;Schmidt et al 2007). Using an Ad-PEGylation approach, we demonstrated that a short artificial peptide selected by phage display, which specifically binds neural precursor cells derived from the hippocampal area of adult mice or rats, was highly effective in targeting NSPCs after virus administration into the brain (Hildebrandt et al 2010;Schmidt et al 2007). These studies also revealed that longterm transgene expression was restricted to precursor cells located in dentate gyrus, while not detected in other injected brain regions such as the SVZ and the ependyma of the lateral ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cells (NSCs) or neuronal progenitor cells with the ability to regenerate functional neural cells have recently drawn more and more attention because of research interests and clinical applications [4][5][6][7]. In vivo, NSCs and neuronal progenitor cells are in an environment that supplies them with repertoire soluble and solid-phase components that regulate cell behavior and function [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%